2010
DOI: 10.1002/meet.14504701243
|View full text |Cite
|
Sign up to set email alerts
|

Emergency knowledge management and social media technologies: A case study of the 2010 Haitian earthquake

Abstract: The US response to the 2010 Haiti Earthquake was a large effort coordinated by three major agencies that worked in tandem with the Government of Haiti, the United Nations, and many countries from around the globe. Managing this response effort was a complex undertaking that relied extensively on knowledge management systems (KMS). For the first time, however, US government agencies employed social media technologies such as wikis and collaborative workspaces as the main knowledge sharing mechanisms. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 14 publications
0
47
0
1
Order By: Relevance
“…Indeed, some studies have shown a close positive association between social media and organizational resilience (Mel et al, 2012;Yates & Paquette, 2011). However, no empirical study, to the best of our knowledge, has examined this relationship within a Korean context.…”
Section: Social Media Use In Emergency Managementmentioning
confidence: 96%
See 4 more Smart Citations
“…Indeed, some studies have shown a close positive association between social media and organizational resilience (Mel et al, 2012;Yates & Paquette, 2011). However, no empirical study, to the best of our knowledge, has examined this relationship within a Korean context.…”
Section: Social Media Use In Emergency Managementmentioning
confidence: 96%
“…Recently, there have been several occasions where social media contributed to raising organizational resilience in Seoul (Liu, 2012). In fact, efforts to adopt and incorporate social media into the field of emergency management have rapidly increased during the last few years (Harman, 2011;Liu, 2012;White, 2011;Yates & Paquette, 2011).…”
Section: The Seoul Floods Of 2013mentioning
confidence: 99%
See 3 more Smart Citations